INFLUENCE WORK DISCIPLINEE IN MEDIATING WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE JOB SATISFACTION - Rizki Wulandari; Moh. Sutoro; Basrowi Basrowi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Employee job satisfaction is a crucial factor influencing an organization's effectiveness in achieving its goals. Job satisfaction is influenced by various factors, including work motivation.work environment, And work disciplineThis study aims to analyze the influence of work motivation andwork environment to work disciplineand employee job satisfaction, as well as testing the rolework disciplineas a mediating variable for employees of the Regional Secretariat of Serang Regency. The study used a quantitative method with a descriptive and verification approach. The study population consisted of 95 employees and all were sampled through a saturated sampling technique (census). Data were collected using a five-point Likert-scale questionnaire and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method using SmartPLS 4.0. The results showed that work motivation had a positive and significant effect on job satisfaction (β = 0.262; p = 0.015) andwork discipline(β = 0.507; p = 0.000).Work environmentalso has a positive and significant effect on job satisfaction (β = 0.293; p = 0.001) andwork discipline(β = 0.427; p = 0.000). Furthermore,work disciplinehas a positive and significant effect on job satisfaction (β = 0.315; p = 0.009). The results of the mediation test show thatwork disciplineable to significantly mediate the influence of work motivation andwork environmenton employee job satisfaction. Therefore, increasing work motivation, creating a conducive work environment, and strengthening work discipline are effective strategies for improving employee job satisfaction at the Serang Regency Regional Secretariat.